KUNJUNGAN LEBAH TUKANG KAYU Xylocopa confusa Linn. (Hymenoptera: Anthophoridae) PADA PERTANAMAN KACANG PANJANG DI KELURAHAN KORONG GADANG KEC. KURANJI KOTA PADANG - Aluvira, Rahma Sri (Pendidikan Biologi, 2014)
Xylocopa confusa or carpenter bees in one type of bee that is included in the ordo Hymenoptera: family Anthophoridae. The carpenter bees nesting in dead wood and bark, which are crucial for the pollination of plants is as. Carpenter bees visting the bean crop to forage in the from of pollen and nectar. Based on the above description of this research has been carried outin march 2014 with the aim to find a carpenter bee visits Xylocopa confusa Linn. (hymenoptera: Anthophoridae). At planting beans di Kelurahan Korong Gadang Kecamatan Kuranji Kota Padang. The study used a descriptive survey method that is by directly observing the visit Xylocopa confusa in the field, field sampling is done at planting beans. Measured weather and light intensity. The area of research is to be a place around Â± 18X11 m. The result showed average number of visits Xylocopa confusa on bean crop di Kelurahan Korong Gadang Kecamatan Kuranji Kota Padang is 38,46 individuals. Number of visit Xylocopa confusa visting on planting beans the most in the morning at 09.00 am average 17 tails, and the aftornoon at 15.00 pm 2,29 average tail, the litle visit during the day at 12.00 average of 1, 43 tail. The number of flowers visited morning between 12,52 and the litle interest in the afternoon aon average between 4,43 interest. Xylocopa confusa visit to the bean crop is highly influenced by the intensity of light. In multivel regression weather factors such as temperature, humidity and wind speed affected the very real connection to the visit of Xylocopa confusa on planting beans.